Macro and microstructural narratives in bilingual children with DLD: A systematic review - Camus Torres, Alondra Elisa; Aparici Aznar, Melina (Revista de Investigación en Logopedia, 2023)
The identification of bilingual children with Developmental Language Disorder (DLD) is complex, and the assessment of narratives may be particularly valuable in this context. Therefore, the aim of this study is to contribute to systematize and disseminate the growing body of literature investigating the narrative skills of bilingual children with DLD through a systematic review guided by the following questions: What aspects at the level of narrative macrostructure and microstructure have been studied in bilingual children with DLD? What features of narrative macrostructure and microstructure differentiate bilingual children with DLD from typically developing bilinguals? What features of narrative macrostructure and microstructure differentiate bilinguals with DLD from monolinguals with DLD? 25 articles were selected from WoS and Scopus databases. Overall, results point to a lower performance both in the bilingual and monolingual DLD population on several measures at both levels, although the core problem is considered to be microstructure. However, there are some contradictory results, so that further research on specific narrative features in both children’s languages is encouraged in order to find clinical markers contributing to a greater efficiency in the assessment of bilingual children. Furthermore, it is suggested that narrative assessment could be combined with other measures to increase the diagnostic accuracy of DLD.
Keywords: narrative discourse; bilingualism; multilingualism; specific language impairment; developmental language disorder